PELATIHAN PENGUATAN KAPASITAS KELOMPOK TANI DENGAN PENGOLAHAN UBI JALAR UNGU DI DESA BARANGKA KECAMATAN KAPONTORI, KABUPATEN BUTON - rejeki, sri; Faradilla, RH. Fitri; L, Mariani; Rianse, Muhammad Iqbal Kusumabaka; Libriani, Restu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2024)
Community service activities in Barangka Village, Kapontori District, Buton Regency aim to improve the skills of farmer groups in processing purple sweet potatoes into value-added food products, namely jam and ice cream. The training, which was attended by 25 participants, was carried out to provide knowledge about the nutritional benefits of purple sweet potatoes, as well as skills in making processed products with economic value. During the activity, participants were taught the process of making purple sweet potato jam and ice cream, from processing raw materials to marketing techniques. The evaluation results showed that 98% of participants succeeded in processing purple sweet potatoes into cendol, and 96% of participants succeeded in making ice cream from the same ingredients. As many as 100% of participants said they liked both products, which shows a high level of satisfaction with this training. This training not only improves the participants' technical skills, but also encourages an entrepreneurial mind-set among farmers, so that they are able to create innovative products that can be produced